KETERAMPILAN GURU DALAM PENGELOLAAN KELAS UNTUK MENINGKATKAN KEAKTIFAN BELAJAR SISWA MELALUI PENDIDIKAN AGAMA KATOLIK DI SMA KATOLIK 2 KABANJAHE - Erikson Simbolon; Sevita Monica Katarina (Jurnal Bahasa Indonesia Prima (BIP), 2023)
This thesis aims to find out the teacher's skills in class management to increase the activeness of student learning in Catholic Religious education subjects. The research method used by researchers is qualitative. Researchers used the results of observations, interviews, and documentation to observe and find out how the skills of teachers in class management increase students' active learning in Catholic Religion education at Kabanjahe 2 Catholic Senior High School. Informants in this research were Catholic religious education teachers as chritical informants, students as supporting informants, and peer teachers as additional informants. Catholic religious education teachers apply skills in classroom management where students are more active than before, starting from students who dare to ask questions, express opinions, and have group discussions. This can be seen from the average value of students' daily tests before the teacher applies skills in class management, namely 72. After the skills that the teacher makes in class management, the average value of students increases to 81 in cycle 1 and then increases again to 84 in cycle 2.